The English you need to know - Bromberg, Murray; Liebb, Julius (New York : Barron's Educational Series, Inc., 1997)
A writing and grammar textbook for the development of reading and composition skills and the introduction of basic grammar and usage.
Includes index.
Keywords: Readers; English language -- Grammar; English language -- Composition and exercises; English language -- Composition and exercises; English language -- Grammar